Proposal for a unified terminology concerning community gradients and boundaries - Erdős, László; Morschhauser, Tamás; Zalatnai, Márta; Papp, Mónika; Körmöczi, László (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
In the fields of synbiology and landscape ecology, terms related to boundaries and gradients are used inconsistently, often resulting in confusion. One of the drawbacks of the lack of a widely accepted terminology is the difficulty that arises when one compares different studies. In this paper, we attempt to define some of the terms linked with gradients and boundaries. First, we distinguish between ecotone and coenotone as well as between ecocline and coenocline. Coenotone and coenocline denote the community gradients, while ecotone and ecocline refer to the gradients of the background factors that cause the community gradients. Then, we consider which gradients should be called tones and which should be called clines. If the gradient is steep, it is a tone (ecotone or coenotone), if less steep, it is a cline (ecocline or coenocline). Next, we differentiate between gradient (transition) and space-segment (transition zone). Finally, we examine cases in which a given transition zone is a boundary at the same time.
Keywords: ecotone; ecocline; coenotone; coenocline; transition zone; edge effect